PENERAPAN TEORI BEHAVIORISME DALAM MENINGKATKAN DISIPLIN DAN KOGNISI DASAR SISWA DALAM PEMBELAJARAN SAINS DI SEKOLAH DASAR - Syah, Pirman; Taslim, Muh.; Hasma; Arifuddin, Kartini Annisa; Damopolii, Muljono; Saprin (Primer Edukasi Journal, 2026)
This study aims to examine the application of behaviorism theory in improving students' discipline and basic cognitive abilities in science learning in elementary schools. The study focuses on stimulus-response-based learning strategies, particularly through repeated practice (drill), direct reinforcement, and providing rapid and specific feedback. This study uses a qualitative approach with a literature review method. Data were collected through searching scientific documents obtained from various sources such as Tandfonline, Routledge, ERIC, Google Scholar, Academia, and national repositories, with the keywords "behaviorism in elementary education", "reinforcement of positive behavior in the classroom", and "basic cognition in science learning". A total of 14 relevant documents were analyzed using the Miles, Huberman & Saldana model which includes data reduction, data presentation, and conclusion drawing. Data validity testing was carried out using the criteria of credibility, transferability, dependability, and confirmability according to Moleong. The results of the study indicate that the behaviorist approach can be applied effectively to form disciplined learning habits and strengthen students' understanding of basic science concepts. With appropriate reinforcement, students show increased attention, responsibility, and active involvement in the learning process. These findings recommend the use of contextual behaviorist principles in science learning in elementary schools to shape positive and constructive learning behavior.